Trainees as change agents in SMEs : experiences from a program for the development of smaller enterprises - Lassinantti, Lars; Ylinenpää, Håkan (Luleå tekniska universitet, Innovation och Design, 1998)
In Sweden, as in most industrialized countries, technology transfer programs and other initiatives aiming at facilitating for smaller firms to utilize the specific expertise universities possess have been common. One example is trainee programs introducing workforce and specialists trained by universities to SMEs. The first Swedish university trainee program directed towards smaller firms started at Luleå University of Technology, and has been running for almost two decades. In this paper we, building on in-depth case studies of two smaller firms supplemented by data from a larger data base, analyze and discuss some experiences from this program, and especially address typical situations where trainees serve different purposes in the development of SMEs. Godkänd; 1998; Bibliografisk uppgift: Presented at American Society for Engineering Management Conference, Virginia Beach, USA, Oct. 1998; 20071127 (ysko)